MADRASAH HEAD PROFESSIONALISM IN OPTIMIZING TEACHER PERFORMANCE AT MA MUHAMMADIYAH LABUHAN LIANG TARANO ACADEMIC YEAR 2022/2023 - faradillah nurul izza (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research was motivated by the author's attention to the decline in teacher performance after the Covid-19 pandemic at MA Muhammadiyah Labuhan Liang and the role of the madrasa head as the highest authority holder in the Madrasah in optimizing teacher performance. This research aims to describe the performance of teachers and the professionalism of the head of the MA Muhammadiyah Labuhan Liang Tarano madrasah in optimizing teacher performance in the 2022/2023 school year. The type of research used is descriptive qualitative which obtains data through observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data examination was carried out using triangulation, namely source triangulation and technical triangulation. The results of this research show that: (1) the performance of MA Muhammadiyah Labuhan Liang teachers can be seen from work discipline and teaching skills, namely skills in making learning plans, skills in carrying out learning and skills in conducting learning evaluations.  (2) The professionalism of the madrasa head in optimizing teacher performance at MA Muhammadiyah Labuhan Liang can be seen from the implementation of his duties and role as leader, motivator and supervisor.